An entrepreneurial perspective on the transition of lignite rural areas to a new regime within a suffocating timeframe - Ilias Makris; Sotiris Apostolopoulos; Eleni E. Anastasopoulou (Administrative Sciences, 2024)
Timetables for energy transition vary across EU Member States. The planning for dealing with the consequences of the transition in affected regions also varies. Under the pressure of the ten-year economic crisis, Greece is one of the few countries that has committed to stop using lignite in electricity generation, achieving 80% by 2023 and definitively by 2028. Apart from its environmental impact, the country assessed using lignite in electricity generation as unprofitable and damaging to the Greek economy. Simultaneously, it formulated a national energy transition plan for the country's lignite areas. The plan also provides support for existing enterprises and incentives for new enterprises. European and domestic financial instruments accompany the support incentives. The compressed timetable is ambitious and demanding, entailing risks of project failure. As one of the first Member State projects to be completed in 2028, its outcome will shape an ambient atmosphere, positive or negative, for other Member States' projects as well. Based on the transition plan and the timelines to which Greece has committed, this research examines the reanimation of rural areas involved in lignite mining from the perspective of entrepreneurship and financial support instruments. The findings revealed that while there is strong social consensus around the design that incorporates best practices, the basis for the completion schedule has unrealistic elements that will have potentially negative consequences for the restoration of the areas that the energy transition affects. The present study highlights the risks for entrepreneurship that tight schedules pose in the context of lignite area redevelopment.
Keywords: 350; energy transition; entrepreneurship; lignite areas; financial instruments